AN ANALYSIS OF THE TENTH GRADE STUDENT’S WRITING ABILITY IN RECOUNT TEXT OF SMA MUHAMMADIYAH 1 METRO ODD SEMESTER ACADEMIC YEAR 2011/2012 - Imam Surya Nugraha (Premise: Journal of English Education and Applied Linguistics, 2012)
The objective of the research is to describe how the students face difficulty in writing ability, to describe what the students face difficulty in making recount text, and to describe the score of students’ in analysis writing ability on recount text. This research is a qualitative descriptive research. The population of this research is the students at the tenth grade of SMA Muhammadiyah 1 Metro in 2011/2012 that consist of 223 students. The sample is 44 students. In taking sample, the researcher uses the cluster proportional random sampling. In collecting the data the researcher uses test, observation, and interview. And in analyzing the data, the researcher uses Alpha Formula.